Mapping Competitive Dynamics Research: A Bibliometric Analysis (2000–2024) - Barišić Radoslav (Business Systems Research)
Competitive dynamics has been a central theme in business, management, and finance research, addressing how firms interact strategically to gain and sustain competitive advantage. Over the past 25 years, this field has evolved significantly, incorporating theoretical and empirical advancements to analyse competitive actions and responses.